A Single Sensor-Based Detection Mechanism for L-L/L-G Faults of PV Array - Murtaza, Ali Faisal; Ahmed Sher, Hadeed; Alharbi, Talal; Spertino, Filippo (IEEE transactions on instrumentation and measurement, 2024)
In this article, a single sensor-based fault detection mechanism (FDM) is proposed to detect the line-to-line (L-L) and line-to-ground (L-G) faults in a photovoltaic (PV) array. The hardware framework contains an extra dc-bus and capacitor-diode pair for each string and a single current sensor. Compared with the past hardware topologies, the proposed FDM delivers the following critical advantages: 1) fault is detected at string level along with its type in milliseconds time frame, which ensures that there is no fire-hazard in PV plant; 2) string under fault automatically disconnects from other healthy strings through passive RC network; and 3) the installation of co-hardware-software system is low cost with negligible active-power field circuits and operates with a simple algorithm. The scientific philosophy and comprehensive analysis of the proposed FDM are provided. To evaluate the effectiveness of the proposed FDM, computer simulations and practical experiments are performed on numerous fault scenarios in a PV array. These results not only validate the fundamental operation of the proposed FDM along with its features but also highlight its excellent accuracy in detecting faults.